Funneliglomus, gen. nov., and Funneliglomus sanmartinensis, a new arbuscular mycorrhizal fungus from the Amazonia region in Peru - Corazon Guivin, Mike Anderson; Cerna Mendoza, Agustín; Guerrero Abad, Juan Carlos; Vallejos Tapullima, Adela; Carballar Hernández, Santos; Alves da Silva, Gladstone; Oehl, Fritz (Verlag Ferdinand Berger & Söhne, 2022)
A new arbuscular mycorrhizal fungus was found in agricultural field sites in the Amazonia lowlands of the Department San Martin, Perú. It was found up to 858 m above sea level in two plantations of the inka nut (also called ‚sacha inchi', Plukenetia volubilis), which was grown in mixed cultures together with Musa sp., Zea mays, Phaseolus vulgaris and Carica papaya. The fungus was propagated in bait cultures in a greenhouse on Sorghum sp., Brachiaria sp., Medicago sativa and Plukenetia volubilis as host plants. The fungus differentiates orange brown to dark orange brown, triple-layered spores, 93-151× 90-148 µm in diameter, terminally on funnel-shaped to rarely cylindrical or slightly inflating hyphae, and a strong, straight to slightly recurved septum that closes the spore pore at the spore base. Phylogenetically, the new fungus represents clearly a new genus in a separated clade, near to Funneliformis and Septoglomus. It can easily be distinguished from all other species of these genera by the characteristic ornamentation of the spore surface, which consists of multiple large, irregular pits. The fungus is here described under the epithet Funneliglomus sanmartinensis, serving as type species of the new genus Funneliglomus.